Practice teaching : a reflective approach - Richards, Jack C. , 1943-; Farrell, Thomas S. C. [ (Thomas Sylvester Charles)] (Cambridge University Press, 2011)
Written for language teachers in training, this book surveys issues and procedures in conducting practice teaching